English Presentation Self-efficacy Development of Indonesian ESP Students: The Effects of Individual versus Group Presentation Tasks - Hartono, Hartono; Mujiyanto, Januarius; Fitriati, Sri Wuli; sakhiyya, Zulfa; Lotfie, Maskanah Mohammad; Maharani, Mega Mulianing (International Journal of Language Education, 2023)
The study aims to investigate the English presentation self-efficacy of ESP undergraduate students through a longitudinal-experimental research design. Rooted in Bandura's social cognitive theory, it addresses two research problems: how Indonesian ESP undergraduate students' English presentation self-efficacy developed when they were exposed to mastery experience in the form of presentation tasks, and how individual and group presentation tasks affected the English presentation self-efficacy development. Three groups of ESP undergraduate students (n = 107) taking ESP English for Management were purposively selected as the participants for the study. Each group was exposed to one of the three forms of interventions: individual presentation tasks, homogeneous-group presentation tasks, and heterogeneous-group presentation tasks. A Likert-type presentation self-efficacy questionnaire validated by exploratory factor analysis (EFA) was utilized to collect the data in Weeks 3, 8, 12, and 16 of the semester. The study found that the Indonesian ESP undergraduate students' English presentation self-efficacy developed significantly as they completed the presentation tasks. The homogeneous-group presentation task outperformed both the heterogeneous-group and individual presentation tasks in enhancing English presentation self-efficacy. Implications for the teaching practices, study limitations, and future research recommendations are presented.